Value marketing as a determinant of forming a political offer in the process of communication between politicians and voters - Widera, Wiktor (Political Preferences, 2018)
At the heart of the concept of value marketing is the evolution of its use. Starting with a mere information about the presence of a product on the market, through subsequently satisfying the needs of the buyer of the product or service, to finally reaching a full dialogue between the bidder (offerer) and the customer. This relationship is based, inter alia, on the common definition of the characteristics of the desired goods and their adjustment to the values indicated by the customers. Also, important values for the buyer of a political product should be similarly shaped in the marketing sense. Creating bonds, the partnership relations between the exchange parties on the political market is a mechanism that makes this process very effective. The article points to the “value” present in the political product and explains how it is created. It also analyses two key contexts of what “value” is, describes marketing and its core tools on the economic and political market. The author of the paper makes a hypothesis that “value” as the core of the political offer generated by the politician-voter relationship is of fundamental importance in political transactions and is at the same time a determinant of electoral decision. Key words: value, value marketing, provision of value, voter, politician, political offer, political market